ANALISIS TERHADAP KEBIASAAN MEROKOK PADA REMAJA DI DESA HATIVE KECIL KOTA AMBON - Bazrul Makatita; Cosalina M Sangaji; Kreshas J.A Noija (Pasapua Health Journal, 2020)
Introduction: Smoking is an activity of sucking a roll of tobacco wrapped in nipa leaves or burning paper, then the smoke is put into the body and exhaled again. In everyday life we can find people who smoke in public places and even around our own home environment. The purpose of this study was “To find out the factors that influence adolescents who do smoking habits in the small hative village of Ambon city” Method: The research method used is qualitative research with a phenomenological approach. Namely research based on postpositivism or enterpretive philosophy, used to examine the condition of natural objects, where the researcher is the key instrument, data collection techniques are carried out by triangulation (combination of observations, interviews, documentation. Result: The results of the discussion obtained from 10 informants where there are 3 factors that influence smoking habits in adolescents, namely family, environment and peers. However, among these 3 factors, peer factors are the most dominant among family and environmental factors. Initially, the teenager only tried smoking to calm his feelings, but after he found relief after smoking, he gradually became accustomed to smoking.